Genetically predicted chronic rhinosinusitis and the risk of stroke: a two-sample Mendelian randomization study - Hu, Jingjing; Wang, Hui; Zhou, Yidan (Frontiers in Neurology, 2024)
Objective: The causal association between chronic rhinosinusitis (CRS) and stroke remains uncertain due to the susceptibility of observational studies to confounding and the possibility of reverse causality. This study aims to examine the potential causal relationship between CRS and the risk of stroke, encompassing various subtypes.Methods: In this research, we utilized genome-wide association study (GWAS) data for CRS from FinnGen. We identified significant single-nucleotide polymorphisms (SNPs) associated with CRS and used them as instrumental variables (IVs). GWAS data for any ischemic stroke (AIS), ischemic stroke (IS), large-artery atherosclerotic strokes (LAS), small-vessel strokes (SVS), cardioembolic strokes (CES), intracerebral hemorrhage (ICH), lobar ICH and nonlobar ICH came from multiancestry GWAS datasets. We conducted two-sample Mendelian randomization (MR) analyses using inverse variance weighting (IVW), weighted median, and MR-Egger regression methods to investigate potential causal relationships between CRS and stroke. Both heterogeneity and pleiotropy were evaluated by sensitivity analyses.Result: The IVW analysis revealed no significant associations between CRS and AIS (OR=0.99, 95% CI [0.93-1.05], P=0.73), IS (OR=0.97, 95% CI [0.81-1.17], P=0.09), SVS (OR=0.96, 95% CI [0.82-1.12], P=0.58), LAS (OR=0.91, 95% CI [0.77-1.08], P=0.09), CES (OR=0.97, 95% CI [0.81-1.17], P=0.79), ICH (OR=1.28, 95% CI [0.74-2.22], P=0.28), lobar ICH (OR=1.22, 95% CI [0.60-2.50], P=0.28) and nonlabor ICH (OR=1.25, 95% CI [0.65-2.40], P=0.79). Sensitivity analysis found no evidence for horizontal pleiotropy. Conclusion: According to genetic evidence, this Mendelian randomization (MR) study does not indicate a causal relationship between CRS and stroke in European populations. However, further studies are necessary to comprehensively evaluate the potential association between CRS and stroke.